The Prophet Windows (The Biblical archaeology review, 2020)
Stained-glass windows adorn many churches. Although the art of making colored (or "stained") glass had existed for millennia, originating in ancient Egypt, it reached a new level of sophistication in medieval Europe. As the demand for stained-glass windows to decorate churches increased, artisans experimented with techniques to produce glass with more colors and fewer […]